Evaluación técnico-financiera del rediseño de la estructura organizacional para el crecimiento de la línea de negocios oilfield services de la empresa Petrogroup Company Ltda (2018)
In the present work, a financial and technical restructuring was carried out in Petrogroup Company Ltda. The work was developed in order to formulate proposals and strategies, both operational and administrative, for the oilfield services business line aimed at improving, promoting and generating greater growth within the company, as well as outside it.